MEASUREMENT OF THE NEUTRAL TEMPERATURE OF THE RAIL PLATE JOINTLESS TRACKS - Rybkin, V. V.; Arbuzov, M. A. (Science and Transport Progress, 2005)
Nowadays the maintenance of long welded rails track is an urgent problem of railway industry. The inexact diagnostic method of the stressed state of long welded rails is used now on railways of Ukraine. This method does not give a direct and true picture of distribution and mode of the stress. Therefore there is a necessity of application of a new diagnostic method, which determines not only temperature stress and stress from longitudinal moving, but also initial and residual, i.e. total longitudinal stress. Taking into account that the rail is made of ferromagnetic material, the phenomenon of magnetic elasticity is used in measurement of mechanical stress. The device for the diagnostic of total mechanical longitudinal stress of static character in a rail is constructed, based on this phenomenon. The technical result of using the new method is an increase in accuracy, speed, convenience and reliability of mechanical stress measurements.